A Study of Some of the Indicators of Noise Pollution in Certain Residential Districts in Fallujah City - Ali, Ahmed H.; Abed, Mohammed M.; Mahdi, Berivan H.; Hussain, Wassan D.; Mohaisen, Aisar M. (Iraqi Journal of Science, 2021)
The aim of this study was to evaluate the effects of noise exposure in certain residential districts in Fallujah city. Twenty-nine stations were selected and divided into two groups; the first group was located 50 to 100 metres from the main streets (quiet areas), whilst the second was located directly on the main streets. Noise levels were measured at a rate of three readings per station for different time periods for approximately sixty days in the year 2020. Mean values were taken in both the morning and evening using a portable sound level meter (Auto range, RS-232). The highest noise level was measured at Alforkan station for the morning reading (83.8 dB) within the second group, while the lowest noise level was measured at Alshohada alawla district station for the morning reading (63.2 dB) within the first group. As for the results of the daily noise level in the evening, the highest daily average (79.4 dB) was measured at Jaish al Shabi street, while the lowest daily average (56.4 dB) was at Dor Alsekak district. The total average noise levels for the morning measurements for the first and second groups were 66.7 dB and 77.2 dB, respectively, whereas those for evening measurements were 65.3 dB and 71.7 dB, respectively. According to field measurements, the average values for the noise (traffic) for the first and second groups in the morning and afternoon exceeded 68 dB, which may cause people to feel very disturbed according to the WHO guidelines on exposure to external environmental noise. In general, all the results measured in this study are above the limits allowed both locally and internationally. This is due to certain erroneous practices in daily activities in addition to the irregular spread of electric generators and commercial activities as well as heavy traffic in the city.